PENGELOLAAN SURAT MASUK DAN SURAT KELUAR BERBASIS WEB PADA JURUSAN ADMINISTRASI NIAGA POLITEKNIK NEGERI UJUNG PANDANG (STUDI KASUS PRAKTEK PENGELOLAAN SURAT PADA MATAKULIAH SIMULASI BISNIS) - Tasya Nurul Aisyah Ramadhani; Eva Aryani; Amiruddin Amiruddin; Imasita Imasita (Journal of Business Administration (JBA), 2022)
One of the practical activities in the business simulation course is the mail management process, which includes: delivery, storage, and archive discovery. Currently, the management of letters in this practice is still manual which results in the use of a lot of time, energy, and costs and frequent errors, scattered or damaged documents. This study aims to produce a website-based letter management application that can facilitate mail management, especially in the practice of managing letters in business simulation courses. The research method used is design research using the waterfall method. The stages or procedures carried out consist of 1) Needs Analysis, 2) Data Collection, 3) System Design, 4) Testing, 6) Implementation. Furthermore, the data collection techniques used are: 1) Interview, 2) Observation. The results of the study indicate that the resulting application can facilitate the management of letters, especially in the use of time, effort and cost.